1987
DOI: 10.1152/jappl.1987.63.1.347
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-entrapped antioxidant enzymes prevent lethal O2 toxicity in the newborn rat

Abstract: Newborn rat pups delivered and maintained in greater than 95% O2 had a lethal time for 50% of population (LT50) of 13 days. Daily intraperitoneal injection per se did not alter the mortality due to inhalation of O2. Survival after 13.5 days of exposure increased from 40 +/- 7% of pups that received buffered saline only to 95 +/- 4% of pups that received liposomes containing superoxide dismutase and catalase. Daily injection of control liposomes containing no enzymes also caused a less dramatic, though signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 14 publications
1
31
0
Order By: Relevance
“…Our study confirmed that injection of 35 S-labelled DNA could be used effectively as a means to monitor DNA distribution after i.t. and i.v.…”
Section: Activity) Expression In All Lobes Of the Right Lung (R1-r4)supporting
confidence: 80%
See 3 more Smart Citations
“…Our study confirmed that injection of 35 S-labelled DNA could be used effectively as a means to monitor DNA distribution after i.t. and i.v.…”
Section: Activity) Expression In All Lobes Of the Right Lung (R1-r4)supporting
confidence: 80%
“…Anti-human factor VIII antibodies were used to identify endothelial cells that line the blood vessels. Figure 6a shows that there was no 35 S-labelled DNA detectable in larger blood vessels. However, in this study, it was not possible to differentiate between epithelial and endothelial uptake of injected DNA in the alveolar region of the lung.…”
Section: Activity) Expression In All Lobes Of the Right Lung (R1-r4)mentioning
confidence: 99%
See 2 more Smart Citations
“…One litter was exclusively exposed to hyperoxia and the other exposed to normoxia. Mothers were alternated between the two rat pup treatment groups every 24 h to prevent previously documented adult rat oxygen toxicity (15) and any inconsistencies in pup nutrition.…”
Section: Methodsmentioning
confidence: 99%